Hepatic Fat Content and Liver Enzymes Are Associated with Circulating Free and Protein-Bound Advanced Glycation End Products, Which Are Associated with Low-Grade Inflammation: The CODAM Study. (14th May 2019) - Bijnen, Mitchell; van Greevenbroek, Marleen M. J.; van der Kallen, Carla J. H.; Scheijen, Jean L.; van de Waarenburg, Marjo P. H.; Stehouwer, Coen D. A.; Wouters, Kristiaan; Schalkwijk, Casper G.
Abstract : Advanced glycation end products (AGEs) accumulate in fatty livers and may contribute to low-grade inflammation (LGI), potentially via their receptor, RAGE. It is unknown if the AGE accumulation in fatty livers results in elevated circulating AGEs. In a cohort study, we investigated the association of liver fat and hepatocellular damage with circulating AGEs and soluble RAGE (sRAGE) and subsequently the association of circulating AGEs and sRAGE with LGI. Cross-sectional associations of liver fat percentage (eLF%; ln-transformed) and liver enzymes (LE score; standardized) with circulating AGEs (free CML, CEL, and MG-H1 in nM and protein-bound CML, CEL, and pentosidine in nmol/mmol lysine; ln-transformed) and sRAGE (pg/ml, ln-transformed) and additionally of AGEs and sRAGE with LGI (standardized) were determined by multiple linear regression. eLF% was positively associated with circulating free CEL (β = 0.090 ; 95% CI 0.041; 0.139) but inversely with protein-bound CML (β = − 0.071 ; 95% CI -0.108; -0.034). Similarly, the LE score was positively associated with free CML (β = 0.044 ; 95% CI 0.012; 0.076) and CEL (β = 0.040 ; 95% CI 0.009; 0.072) but inversely with protein-bound CML (β = − 0.037 ; 95% CI -0.060; -0.013). Free CML (β = 0.297 ; 95% CI 0.049; 0.545) was positively associated with LGI, while protein-bound CML (β = − 0.547 ; 95% CI -0.888; -0.207) was inversely associated, although this association was absent after adjustment for BMI. eLF% and LE score were not associated with sRAGE and sRAGE not with LGI after adjustment for BMI. Liver fat and enzymes were positively associated with circulating free AGEs, which were associated with LGI. In contrast, inverse relations were observed of liver fat and enzymes with circulating protein-bound AGEs and of protein-bound AGEs with LGI. These data suggest that hepatic steatosis and inflammation affect the formation and degradation of hepatic protein-bound AGEs resulting in elevated circulating free AGE levels. These alterations in AGE levels might influence LGI, but this is likely independent of RAGE.